Petrogenesis of post-collisional mesozonal enderbite in the Proterozoic Chhotanagpur Gneissic Complex, Eastern India: Implications of slab-break-off - Poulami Roy; Bapi Goswami; Ankita Basak; Chittaranjan Bhattacharyya (Solid Earth Sciences)
Collisional orogeny produces large volumes of tonalitic melts at two stages: first, during the oceanic subduction below the continent (continental arc), and again, during the post-collisional stage. In a polydeformed and polymetamorphosed terrain, it would be challenging to distinguish between arc tonalites and post-collisional tonalites (and their metamorphosed equivalents, enderbites). The Chhotanagpur Gneissic Complex (CGC) belongs to the EW to ENE-WSW tending, 1500 km long Grenvillian collisional belt amalgamating the North and South Indian cratonic blocks. We discuss the field disposition, petrography, mineral chemistry, geochemistry, the physical condition of crystallization and metamorphism, and the petrogenetic model of enderbites from the CGC. Enderbites sporadically occur as cm-to-dm-thick leucosomal bands in migmatitic gneisses (migmatitic enderbites) and as small stock-sized plutons (massive enderbites) intruding migmatitic gneisses. Both of these types intruded before the end of the regional deformation. Both the massive and migmatitic enderbites predominantly contain plagioclase, quartz, biotite (with a higher abundance in the migmatitic type), minor orthopyroxene, clinopyroxene, hornblende, K-feldspar, and accessories such as opaque minerals, apatite, and zircon. Garnets rarely occur in migmatitic enderbites. Thermodynamic modeling suggests a low liquidus temperature (∼750 °C), intermediate pressure of emplacement (∼5.5 kb), moderate oxygen fugacity (ΔQFM = +1 to +2), and low water (∼4.0 wt%) of the parental tonalite magma. The two enderbite types have been derived from two distinct crustal (amphibolites) sources by water-fluxed partial melting at <10 kb pressure, shallower than the garnet stability field. About 20–40 % of batch-melting of shoshonitic basaltic sources yielded migmatitic enderbites, while about 40–70 % of batch-melting of within-plate basaltic sources produced massive enderbites. Discrimination diagrams display a post-collision tectonic setting of these enderbites. The migmatitic enderbites and magma of enderbite plutons formed during regional anatexis due to thermal relaxation in the lower crust after attaining peak pressure during the decompressive phase of regional granulite facies metamorphism (1000–950 Ma) related to slab breakoff at the post-collisional stage of the orogeny. Mantle-derived magmas formed by adiabatic decompression in the upper mantle supplied the heat.